'Good for the country, beneficial to the family': the Bắc Hưng Hải irrigation system and pragmatic collectivism in post-1954 northern Vietnam. (3rd July 2022) - Pham, Thi Hong Ha
ABSTRACT: Focusing on the construction of the Bắc Hưng Hải irrigation system ( Đại thủy nông Bắc Hưng Hải ) in socialist northern Vietnam in the late 1950s, this article examines the statecraft of the government of the Democratic Republic of Vietnam (DRV) as it sought to build socialism in the post-1954 period. To mobilize the free labour of local workers ( dân công ) to construct the massive irrigation system, the DRV's key strategy was to encourage workers to embrace a moral value that I term 'pragmatic collectivism'. In official narratives about Bắc Hưng Hải, the labour service of local workers embodied not only their voluntary contribution to collective interests, i.e. the benefits of others, the country and socialism, but also their righteous pursuit of the immediate benefits of themselves, their families and villages. While this state-sanctioned version of collectivist morality shared remarkable similarity with the universal value of collectivism widely upheld in other socialist contexts, particularly the Soviet Union and China, it also incorporated elements much in contrast with Soviet-style collectivism, notably the treatment of the pursuit of individual and family benefits as in harmony with, rather than in conflict with, the pursuit of collective interest.